JUMPA Vol.2 No.3 Okt 2015 PENGARUH PENDIDIKAN DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN: PENGARUH PENDIDIKAN DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN - Laurencia S. Krismadewi Universitas Mercu Buana, Jakarta (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2015)
The purpose of this study is to determine the effect of education and work experiences to employee performance at PT. Global Informasi Bermutu. Descriptive quantitative research methods by using statistical correlation an multiple regression with the aim of analyzing the effect of the two independent variables (Education and Work Experiences) on the dependent variable (Employee Performance). The sample used was an employee of employees as much as 240 respondents who made a sample random determination. The result research showed that from the analysis are known, also demonstrated from regression technique and significance, which states that both partially and jointly a positive and significant of employee performance. From two independent variables, the education has the most dominant influence on employee performance.